The big squeeze tough times for the American worker - Greenhouse, Steven (Alfred A. Knopf, 2008)
A look at the stresses and strains faced by American workers as wages have stagnated, health and pension benefits have grown stingier, and job security has shriveled. Workplace journalist Greenhouse explores why, in the world's most affluent nation, so many corporations are intent on squeezing their workers dry. The book explains how economic, business, political, and social trends--among them globalization, the influx of immigrants, and the Wal-Mart effect--have fueled the squeeze. We see how the post-World War II social contract that helped build the world's largest and most prosperous middle class has been replaced by a startling contradiction: corporate profits, economic growth, and worker productivity have grown strongly while worker pay has languished. Greenhouse also examines companies that are generous to their workers and can serve as models, and presents a series of pragmatic suggestions on what government, business, and labor should do to alleviate the squeeze.--From publisher description.